Comparison Of Starting Speed With And Without The Use Of The Regulatory Flag In Professional Soccer Assistant Referees - Díaz Escobar, Cristian (2025)
Introduction: Sprinting in soccer is a frequent and determinant motor action. Professional assistant referees use this movement, especially in key plays of the match. Objective: To analyze the starting speed performance for a 10-meter linear stretch in professional assistant referees, with and without the use of a flag. Methodology: A quantitative, explanatory, correlational cross-sectional design was applied to 42 subjects (4 women: 37 + 1.41 years, 1.6 + 0.03 m, 56.58 + 3.65 kg - 38 men: 36.11 + 4.57 years, 1.74 + 0.05 m, 72.77 + 7.13 kg) belonging to the National Association of Professional Soccer in Chile. Three sprints were requested without and with flag, and the time was recorded with Microgate Witty-Gate photocells. Results: In males, there were significant differences in a couple of registers for the group analysis and by category (p<0.05), in addition to a cubic curve behavior in the regression equations for speed and age. However, the data in general established that there would be a homogeneous speed performance in the assistant referees during the sprints with and without the use of the flag; in the case of the female assistant referees, only a descriptive analysis was performed due to the size of the sample. Conclusion: The use of the flag in a group of professional assistant referees would not influence the starting speed for a 10-meter stretch, considering that it is an element of compulsory use in soccer matches and implies adapting the running technique.